2003
DOI: 10.1021/ja028674s
|View full text |Cite
|
Sign up to set email alerts
|

Size-Tunable Emission from 1,3-Diphenyl-5-(2-anthryl)-2-pyrazoline Nanoparticles

Abstract: Organic nanoparticles of 1,3-diphenyl-5-(2-anthryl)-2- pyrazoline (DAP) ranging in average diameters from 40 to 160 nm were prepared through the reprecipitation method. The average diameters of the particles were controlled by variation of the aging time. We found that DAP nanoparticles exhibit the size-dependent optical properties. The absorption transitions of the nanoparticles at the lower-energy side experience a bathochromic shift with an increase in the particle size as a result of the increased intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
186
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(192 citation statements)
references
References 31 publications
6
186
0
Order By: Relevance
“…Yao et al reported the size dependence of emission spectra for pyrazoline nanoparticles. 11 The fluorescence peaks shift to red increasing the particle size. They concluded that the 55 effects originated from the formation of charge transfer excitons, depending on the particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al reported the size dependence of emission spectra for pyrazoline nanoparticles. 11 The fluorescence peaks shift to red increasing the particle size. They concluded that the 55 effects originated from the formation of charge transfer excitons, depending on the particle size.…”
Section: Introductionmentioning
confidence: 99%
“…The size-dependent optical properties have been widely studies by several groups. [5][6][7][8][9][10][11][12][13][14][15][16] Asahi and Masuhara et al precisely studied the relation between the optical properties and crystal size by using single particle fluorescence spectroscopy coupled with atomic force 50 microscopy (AFM). 7,8 It is found that the size dependence is correlated well to the surface-to-volume ratio of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Kasai and Nakanishi et al first reported that the fluorescence spectra of perylene nanocrystals, which were prepared by the reprecipitation method, depended on their size, and the fluorescence spectra of the nanoparticles differ from that of the bulk crystals [2,3]. There are many reports about organic nanoparticles in the past decade [4][5][6][7]. They proposed lattice softening of the nanoparticles as a cause of the size-dependent optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed lattice softening of the nanoparticles as a cause of the size-dependent optical properties. Yao et al reported the size dependence of the emission spectra for pyrazoline nanoparticles, which originated from the formation of charge transfer excitons due to the flexibility and various inter-and intramolecular overlapping structures in the nanoparticles [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation